DAMPAK TAMAN WISATA TALANG INDAH TERHADAP PEREKONOMIAN MASYARAKAT DI KABUPATEN PRINGSEWU - Romaniartini Desiwi; Fembriarti Erry Prasmatiwi; Lina Marlina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
Talang Indah Tourism Park is a tourist attraction located in Pringsewu Regency. The purpose of this research is to analyze the impact of Talang Indah Park on the economy of the people in the Pringsewu Regency. The research method used was a survey method with 75 visitor respondents, 12 business actors, and 23 labor respondents.  The data analysis method used is the Keynesian multiplier effect, by calculating the direct impact, indirect impact, and induced impact.  This study concludes that the direct impact that is felt is IDR24,405,000.00 per month, the indirect impact is IDR35,770,000.00  per month, and the induced impact is IDR42,402,000.00 per month. The Keynesian Income Multiplier value at Talang Indah Park is 5.20, so it can be concluded that Talang Indah Tourism Park has economic impact on tourism activities.Key words: direct, indirect, induced, multiplier effect, tourism park